Parents' management of adolescent patients' postoperative pain after discharge: A qualitative study - William Dagg; Paula Forgeron; Gail Macartney; Julie Chartrand (Taylor & Francis Group, 2020)
Background: Short hospital admission periods following pediatric inpatient surgery leave parents responsible for managing their child's postoperative pain in the community following discharge. Little is known about the experiences of parents caring for their child's postoperative pain after discharge home following inpatient surgery. Research examining parental postoperative pain management following their child's day surgery has found that parents are challenged in their pain management knowledge and practices. Aims: This interpretative phenomenological analysis study sought to understand parents' experiences caring for their child's postoperative pain at home. Methods: Semistructured telephone interviews were conducted with seven parents between 2 weeks and 6 months after their child's discharge from hospital. Results: Identified themes were coming home without support, managing significant pain at home, and changes in the parent-child relationship. Conclusions: Parents could potentially benefit from nurses optimizing educational interventions, from receiving ongoing support of transitional pain teams, and from assistance with return to school planning.